Pengaruh Keselamatan dan Kesehatan Kerja Terhadap Produktivitas Kerja Karyawan Pada PT. Johnline Baratama Site Konawe di Sulawesi Tenggara - Mukhtar Galib; Sinaruddin Sinaruddin (STIM LASHARAN JAYA MAKASSAR, 2021)
The research intends to understand the impact of Occupational Health and Safety (K3) as well as work supervision on the performance of operational employees (study at PT. Johnline Baratama Site Konawe). Descriptive analysis method with Likert scale for descriptive analysis, while for verification analysis using the coefficient of determination, multiple correlation, and regression testing. Questionnaires were distributed to 97 employees. The questionnaire was tested with validity tests, reliability tests, and also classical assumptions. The results of the research illustrate that simultaneously occupational health and safety and work supervision have a positive and significant impact on the performance of employees of PT. Johnline Baratama Site Konawe. While partially occupational health safety has a positive and significant influence on employee performance at PT. Johnline Baratama Site Konawe and work supervision have a positive and significant impact on the performance of PT. Johnline Baratama Site Konawe.